ACUTE TOXICITY TESTING OF NEWLY DISCOVERED POTENTIAL ANTIHEPATITIS B VIRUS AGENTS OF PLANT ORIGIN - Gm, Subaiea; M, Aljofan; Vr, Devadasu; Tm, Alshammari (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Our previous studies indicate that alkaloids could be developed as potential antihepatitis B agents. In the present study, we investigated the in vitro antihepatitis B virus (HBV) activity and in vivo acute oral toxicity of three isoquinoline alkaloids [-(-) Canadine, Corydadine, and Berberine] obtained from Fumaria and Corydalis species. The compounds were selected based on their therapeutic indexes calculated previously in vitro. Methods: The antiviral activity and cytotoxicity of selected isoquinoline alkaloids were evaluated in vitro in HepG2 cells. In vivo, acute oral toxicity was performed in female mice following the Organization for Economic Cooperation and Development test guideline-423 (acute toxicity class method). Results: The selected agents have shown high antiviral activity against HBV and low cytotoxicity in vitro. The results obtained from an acute oral toxicity study revealed that the LD50 of all the test compounds was >2000 mg/kg when administered orally to mice. All the tested compounds fall under the category 5 (unclassified) according to the Globally Harmonized System, with a LD50 value >2000 mg/kg when orally administered to mice. Conclusion: The results of the study revealed that OR-13 and MNAD can be studied further and can be developed as antihepatitis B drugs.